Pulmonary tuberculosis and non-recent immigrants in Japan - some issues for post-entry interventions - Lisa Kawatsu; Kazuhiro Uchimura; Akihiro Ohkado; Seiya Kato (World Health Organization Regional Office for the Western Pacific, 2017)
Foreign-born persons are considered one of the high-risk populations for tuberculosis (TB), and numerous studies have discussed the potential role of pre-entry TB screening for immigrants. However, rates of TB disease among immigrants can remain high several years after entry. In Japan, approximately 50% of TB among foreign-born persons occurs among those who have entered Japan more than five years before being diagnosed, i.e. non-recent immigrants. However, little attention has been paid so far to the issue of TB control among the non-recent immigrants. A detailed analysis of the Japan Tuberculosis Surveillance data was therefore conducted to describe the characteristics of TB among non-recent immigrants and discuss policy implications in terms of post-entry interventions in Japan. The main findings were as follows: 1) the proportion of pulmonary TB cases aged 65 years and older was higher among non-recent than recent immigrants (9.8% vs 1.2%); 2) the proportion of those with social risk factors including homelessness and and being on social welfare assistance was higher among non-recent than recent immigrants; and 3) the proportion of those detected via routine screening at school or workplace was significantly lower among non-recent immigrants aged between 25 and 64 than among recent immigrants in the same age group (15.4% vs 28.7%). Our results suggested the need to increase the opportunities for and simultaneously improve the take-up rate of community-based screening for non-recent immigrants.